Monkey bartop stand / Danish Hazriq Yusaini ...[et al.] - Yusaini, Danish Hazriq; Johari, Adib Iskandar; Haslan, Muhammad Al-Amin; Jainal, Ahmad Fahmi; Abul Jalil, Nurul Izzah
During this pandemic era, we saw a lot of people are experiencing a work from home routine. Students and workers will held their classes or meeting through google meets, zoom or webex. This can lead to frequent use of mobile technologies such as telephones and laptops. Laptops are the most frequent use equipment by students and workers. However, the use of a laptop for too long will cause pain in some parts of the body such as the shoulders, back and wrists. Not only that, we also facing a problem where our outdoor exercise routine are limited. Therefore, it is suitable for us to have an indoor exercise routine in the house in order to keep a healthy lifestyle. To overcome all this problem, we decided to produce a prototype called “Monkey Bartop Stand”. This mechanical performance product is a laptop stand that can be used as an exercise equipment at the same time. This prototype solves the mechanical equations providing the values required. Features included in this product include the ability to adjust the height during the use of the laptop stand and the frame are able to rotate according to the comfort of the user. We also apply a safety factor in our product for example when the users wanted to use it as an exercise equipment. Material use for our prototype is stainless steel considering how the prototype are function. This product can encourage consumers to exercise regularly even if they have to face constraints to work from home. We are also confident that through this product we can make consumers aware of the importance of adopting a healthy lifestyle.